Analisis Manajemen SDM Dalam Mengembangkan Strategi Pembelajaran Di Era New Normal - Syamsul Bahri; Novira Arafah (Tafkir: Interdisciplinary Journal of Islamic Education, 2020)
This literature study was conducted to find out: Analysis of Human Resource Management in Improving Strategies Learrning in the New Normal Era. In this research, the method used qualitative with a library research. The results of the study indicate are: Human Resource management in improving strategies learrning in the new normal era is effort, mature readiness, provisioning both in terms of IT skills and virtual learning progress. The most appropriate learning strategy in the new normal era is to follow the rules of the Ministry of Education and Culture with virtual learning through agreed platforms. For this reason, the 2 main elements of teaching and learning activities take place, these students and teachers must be equipped, qualified and know the direction of learning that will be filtered in order to minimize misunderstanding between teacher and students. While students at home, study is assisted and supervised by their parents to avoid deception, laziness and cheating during the exam. So that ethics, values ​​/ norms remain upheld in the world of academia.